2019
DOI: 10.1101/629667
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global ribosome profiling reveals that mutant huntingtin stalls ribosomes and represses protein synthesis independent of fragile X mental retardation protein

Abstract: The regulators that stall ribosome translocation are poorly understood. We find that polyglutamine-expanded mutant Huntingtin (mHtt), the Huntington's disease (HD) causing protein, promotes ribosome stalling and physiologically suppresses protein synthesis. A comprehensive, genome-wide analysis of ribosome footprint profiling (Ribo-Seq) revealed widespread ribosome stalling on mRNA transcripts and a shift in the distribution of ribosomes toward the 5' end, with single-codon unique pauses on selected mRNAs in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 70 publications
1
22
0
Order By: Relevance
“…As we wrote this manuscript a study was published that suggested 335 Htt has a physiological function of binding to ribosomes and slowing the speed of ribosome 336 translocation of many target mRNAs [32]. Intriguingly, mutant Htt further slowed protein synthesis rates 337 [32]. These data suggest that Httex1 may be slowing translation in trans rather than in cis (through 338 nascent Httex1-driven stalling).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…As we wrote this manuscript a study was published that suggested 335 Htt has a physiological function of binding to ribosomes and slowing the speed of ribosome 336 translocation of many target mRNAs [32]. Intriguingly, mutant Htt further slowed protein synthesis rates 337 [32]. These data suggest that Httex1 may be slowing translation in trans rather than in cis (through 338 nascent Httex1-driven stalling).…”
mentioning
confidence: 96%
“…Our data here suggests that expression of Httex1, at wild-type or mutant polyQ lengths, does not stall 334 on the ribosome during translation. As we wrote this manuscript a study was published that suggested 335 Htt has a physiological function of binding to ribosomes and slowing the speed of ribosome 336 translocation of many target mRNAs [32]. Intriguingly, mutant Htt further slowed protein synthesis rates 337 [32].…”
mentioning
confidence: 99%
“…For the first time, we applied high-resolution ribosome sequencing technology to genetically precise knock-in HD cell models: immortalized STHdh Q7/Q7 (control), STHdh Q7/Q111 (HD-het), and STHdh Q111/Q111 (HD-homo) striatal neuronal cells, derived from WT, Hdh Q7/Q111 , and Hdh Q111/Q111 mouse embryos (37). We successfully generated high-quality reads and found new roles for HTT as a physiological suppressor of translational elongation by regulating ribosome movements (38). In global ribosome profiling data, we found that cGAS showed a high ribosome occupancy (ribosome protected fragments (RPF)/mRNA) estimated by ribosome protected fragments (RPF) counts in exon 1 in HD-het and HD-homo cells, while there were fewer reads in control cells ( Fig.…”
Section: Ribosome Profiling Data Revealed High Ribosome Occupancy In mentioning
confidence: 99%
“…1C, arrow) and 172 (CGT)) in HD cells. The RFP/mRNA analysis of other known DNA sensors such as Toll-like receptor 9 , which is mostly restricted to blood and immune cells (40), is not expressed in striatal cells (38). The absence in melanoma 2 (AIM2), another cytosolic DNA sensor (41), is also induced in HD cells, but to a much smaller extent compared to cGAS (the ratio of RFP/mRNA for cGAS is 14 whereas for AIM2 it is 2.2) ( Fig.…”
Section: Ribosome Profiling Data Revealed High Ribosome Occupancy In mentioning
confidence: 99%
See 1 more Smart Citation